Parental Attitudes, Motivators and Barriers Toward Children’s Vaccination in Poland: A Scoping Review - Krystyna Szalast; Grzegorz Józef Nowicki; Mariola Pietrzak; Agnieszka Mastalerz-Migas; Aleksander Biesiada; Elżbieta Grochans; Barbara Ślusarska (Vaccines)
Background: Vaccination is one of the most effective ways of protecting individuals against serious infectious diseases and their fatal consequences. Objectives: The aim of this scoping review was to synthesize data on parental attitudes toward vaccination and identify factors influencing the motivators and barriers to children’s vaccination based on Polish studies. Methods: The scoping review process and reporting were based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScRs) checklist. In the period between January 2014 and July 2024, the following databases were searched for publications: PubMed, Web of Science, Cochrane, Ebsco, and Scholar Google. Results: A total of 1531 potentially relevant records were reviewed, and 30 original publications from research samples collected in Poland were selected. According to the findings, vaccination rates varied between 100% and 70%, with parental acceptance levels for mandatory vaccination ranging from 99% to 65%. Parents most commonly cited the physician, the nurse, and the Internet as their primary sources of vaccination-related information. Moreover, parental primary motivators for vaccinating their children were prevention against infectious diseases, the opinion that vaccines are safe, and the belief that childhood vaccination is right and effective. The major barriers to vaccination were fear of vaccine side effects and the belief that vaccines are ineffective. Parents that were better educated, were of younger age, lived in cities, and had a higher income were much more likely to vaccinate their children. Conclusions: Understanding parental attitudes toward vaccination may help develop an educational program aimed at combating misinformation and increasing childhood vaccination coverage rates.